Paul Horn (1863‑1908) : misère et splendeur d’un iranisant et turcologue à Strasbourg - Johann Strauss (Recherches Germaniques)
The paper intends to present the life and the works of the distinguished Iranian scholar Paul Horn (1863-1908). A native of Saxony in Eastern Germany, he spent most of his life in Strasbourg where he also died, at an early age, and completely exhausted, in 1908. The biography of this scholar is, in many respects, exemplary. Within two decades, Paul Horn was able to accumulate an enormous amount of competence enabling him to publish remarkable works not only in the field of Iranian studies but also in that of a more recent academic discipline, turcology (where Horn has to be considered as a pioneer). We find in his life both the hardships of a Privatdozent (unsalaried lecturer) at the prestigious Kaiser-Wilhelms-Universität, the necessity to ask permanently for grants and subsidies, and ambitious publication projects such as the Persian divan of Sultan Selim I. Paul Horn represents a perhaps typical case of German oriental scholarship at that time. This scholarship is characterized by versatility, the capacity to penetrate into the most diverse fields of research—sometimes with an amazing rapidity—and to produce works of fundamental importance. Archival documents further provide us with a great number of elements which can illustrate the very special relationship of these scholars with the countries presenting the focus of their research, i.e. the “Orient”.